Image is nothing self is everything : a study on the values and images portrayed by the youth in TV softdrink commercials and their influence on the self-perception of the youth - Carbonel, Ernest Kristian A.
This descriptive study seeks to find out how the portrayals of the youth in TV softdrink commercials affect one's self-perception. Using a one-shot survey design and content analyses of three TV ads, the researcher was able to identify the traits of the youth in these commercials as well as the characteristics of the youth today. 150 respondents were randomly selected from five different schools in the University Belt area and Diliman-Katipunan are for the survey. The respondents also answered the Pasao Self-concept scale so that the researcher would be able to measure their self-perception. The researcher's analyses of the three commercials showed that the youth were very out-going, as well as innovative in the way they handled situations they were faced with. However, the commercials also illustrated how the youth had much insecurity, such as their openness to foreign influence, which led to their lack of Filipino values. The results revealed that there was a relationship between the portrayals of the youth in the commercials and the self-perception of the respondents, and this had a lot to do with the frequency of having watched the commercials. As the frequency of watching the commercials increase, so does one's self-perception. The researcher also learned that the socio-demographic characteristics played a role in affecting one's self-perception. One's gender, age and monthly family income were also reasons why the respondents had generally high levels of self-concept. From this study the researcher was able to prove that there is a positive relationship between the portrayals of the youth in these ads and the seld-perception of the youth audience.